Restauración y puesta en funcionamiento de 2 turbinas eólicas verticales ubicados en la UAN sede Tunja-Boyacá (2022)
Taking into account that efficient energy production systems are required, which do not depend on conventional fuels, in order to make use of renewable resources, the Antonio Nariño de Tunja University has designed a system of two vertical turbines that has been affected by erosive processes related to wind and rain, so that before this project it was out of service. Based on the above, and as presented in the objective of this work, a process was carried out that allowed the restoration of two vertical wind turbines with commissioning at the Antonio Nariño Sede Tunja university.